Election promises on children's wellbeing and health 2015 to 2021 – a study of Finnish voting advice applications database. Issue 8 (December 2022) - Hiilamo, Aapo; Ristikari, Tiina; Helve, Otto; Kaila, Minna; Jalonen, Harri; Virtanen, Petri
Background: According to the UN Convention on the Rights of the Child, children's views should be heard in policymaking. But it remains unclear to what extent children's wellbeing is considered in election promises Methods: We investigated the extent to which Finnish political candidates consider children and their wellbeing in their election promises. We used YLE, the national broadcaster's voting advice application database, and analysed some 35, 000 politicians' election promises made in the 2015 and 2019 parliamentary and the 2017 and 2021 municipal elections. We calculated the proportion of candidates who mentioned children and examined the content of the election promises in which children were mentioned. Logistic regression models were used to examine the role of the background of the characteristics of candidates. Results: In the 2015 and 2019 elections, some 12% and 19% of candidates, respectively, mentioned children in their election promises. The figures for the 2017 and 2021 municipal elections were higher at 19% and 24%, respectively. In the 2021 election, the candidates considering children in their election promises were younger and had higher education qualifications. Inspection of a random set of 350 promises indicated that common issues mentioned in respect of children were education and hobby activities. Concrete proposals to improve the wellbeing of children were rarely put forward. Conclusions: Political candidates are increasingly considering children in their election promises but concrete proposals to improve the wellbeing and health of children are rare. Effective policy solutions to improve the health of children should be discussed in election debates.